Czy tłumacz może pozwolić sobie na czułość? Spieszczenia a ekwiwalencja emocjonalna w przekładzie literackim - Jarniewicz, Jerzy (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
One of the most frequent problems in translation is the question of translation of hypocorisms: inasmuch as Polish is rich in diminutives, English practically does not have them. Diminutive and affectionate forms in a very limited range of contexts, and descriptive (analytical) diminutives are of little stylistic interest. The article discusses examples of coping with this problem in translations both from Polish into English, and from English into Polish. The authors tries to answer the question if it is possible to retain the emotionality expressed in diminutives of a translated text. Two texts were selected for the analysis: Jan Kochanowski’s Laments in Stanisław Barańczak and Seamus Heaney’s translation, and Ronal Fairbank’s The Flower Beneath the Foot, translated by Andrzej Sosnowski. Laments, addressed to a dead child, are of particular interest for the analysis, because diminutives and terms of endearment are frequently used and perform a peculiar function of creation of meaning. Discussing this translation, the author of the article tries to demonstrate that the emotionality expressed by Kochanowski through hypocorisms has been expressed by other means in the English translation: the right choice of epithets, and orchestration of the verse. In the Polish translation of Firbank’s novel, the hypocorisms introduced by the translator are read not as an arbitrary addition, but as elements that contribute to the camp climate of the novel, and reflect the irony, artificiality, and theatricality of the work, by means that are accessible in Polish language.